Design of RCPC Encoded V-BLAST MIMO System - Lydia Sari; Gunawan Wibisono; Dadang Gunawan (Journal of ICT Research and Applications, 2009)
A Vertical Bell Laboratories Layered Space-Time Multiple-Input Multiple Output (V-BLAST MIMO) enhanced with Unequal Error Protection (UEP) to achieve highly reliable wireless communication is proposed. The UEP scheme is based on Channel State Information (CSI) available at the transmitter whose calculation utilizes Singular Value Decomposition (SVD) of the MIMO matrix channel. Using Rate-Compatible Punctured Convolutional (RCPC), a different code rate is given for each sub-stream of source information, according to its level of transmit power. To analyze the system performance, an analytical BER comprising the performance of V-BLAST MIMO BPSK-modulated signals and the performance of RCPC codes in Rayleigh fading environment is presented. Simulation results show that increasing the code rate can attain a bandwidth efficiency of 33.3% in expense Eb/No, but this penalty is not severe as the high code rate is used in sub-channels with high attenuation level. It is also shown that a system with 2 transmit and 4 receive antennas will have an improved performance within only 1 dB range compared to a system with 2 transmit and 2 receive antennas. The performance of the proposed system is mostly affected by the type of puncturing matrices chosen.